Increased circulating uric acid aggravates heart failure via impaired fatty acid metabolism - Bowen Lou; Haoyu Wu; Hannes Ott; Katrin Bennewitz; Chen Wang; Gernot Poschet; Hui Liu; Zuyi Yuan; Jens Kroll; Jianqing She (Journal of Translational Medicine, 2023)
Abstract Background Increased circulating uric acid (UA) concentration may disrupt cardiac function in heart failure patients, but the specific mechanism remains unclear. Here, we postulate that hyperuremia induces sterol regulatory element binding protein 1 (SREBP1), which in turn activate hepatic fatty acid biosynthesis response, leading to cardiac dysfunction. Methods and results Increased circulating uric acid was observed in heart failure patients and inversely correlated to cardiac function. Besides, uric acid correlated to circulating lipids profile based on metabolomics in heart failure patients. Using cultured human hepatoellular carcinomas (HepG2) and Tg(myl7:egfp) zebrafish, we demonstrated that UA regulated fatty acid synthase (FASN) via SREBP1 signaling pathway, leading to FFA accumulation and impaired energy metabolism, which could be rescued via SREBP1 knockdown. In ISO treated zebrafish, UA aggravated heart failure via increased cardiovascular cavity size, decreased heart beats, pericardial edema and long-stretched heart deformation. Conclusions Our findings suggest that UA-SREBP1-FASN signaling exacerbates cardiac dysfunction during FFA accumulation. Identification of this mechanism may help in treatment and prevention of heart failure.